2021
DOI: 10.3390/ijms222212145
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Role of Connexins and Gap Junctions Channels in Adipose Tissue and Obesity

Abstract: Due to the inability to curb the excessive increase in the prevalence of obesity and overweight, it is necessary to comprehend in more detail the factors involved in the pathophysiology and to appreciate more clearly the biochemical and molecular mechanisms of obesity. Thus, understanding the biological regulation of adipose tissue is of fundamental relevance. Connexin, a protein that forms intercellular membrane channels of gap junctions and unopposed hemichannels, plays a key role in adipogenesis and in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 136 publications
(165 reference statements)
0
5
0
Order By: Relevance
“…During the initial process of fat formation, connexins are highly phosphorylated. In the intermediate state of adipocyte differentiation, Cx43 is translocated from the membrane and phosphorylation is reduced by proteasome degradation [ 52 ]. In the DEI PPI networks of TF and SF, the hub isoforms, including XM_012180724.3, NC_056054.1.4780.11, NC_056064.1.197.5, NC_056064.1.1711.2, and isoforms XM_012180724.3, NC_056054.1.4780.11, NC_056064.1.1711.2, and Xm_015093599.3, were all enriched in the Proteasome KEGG pathway.…”
Section: Discussionmentioning
confidence: 99%
“…During the initial process of fat formation, connexins are highly phosphorylated. In the intermediate state of adipocyte differentiation, Cx43 is translocated from the membrane and phosphorylation is reduced by proteasome degradation [ 52 ]. In the DEI PPI networks of TF and SF, the hub isoforms, including XM_012180724.3, NC_056054.1.4780.11, NC_056064.1.197.5, NC_056064.1.1711.2, and isoforms XM_012180724.3, NC_056054.1.4780.11, NC_056064.1.1711.2, and Xm_015093599.3, were all enriched in the Proteasome KEGG pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, adipogenic differentiation has been shown to trigger the formation of lipid droplets, significantly reducing the cellular cytoplasmic space and leading to morphological hypertrophy [52,53]. Cells in this hypertrophic state exhibited a weakened response to shear stress and external stimulation, with notable reductions in the expression of junction proteins such as Connexin 43 on the cell surface, resulting in diminished adhesive capacity and very low host tissue integration [54]. Moreover, adipogenesis down-regulates RhoA activity, inducing the depolymerization of stress fibers into the G-actin monomer state [14].…”
Section: Spheroid Fusion For the Fabrication Of Macro-sized Adipose T...mentioning
confidence: 95%
“…Adiponectin is not the only promising target with other metabolic targets involved in connexin and gap junction signalling already highlighted. 157 Yet, overall, the highly complex metabolic–immunological–autonomic cardiac interactions and their contribution to ventricular arrhythmogenesis are still poorly understood.…”
Section: Emerging Therapeutic Targets and Novel Concepts For Precisio...mentioning
confidence: 99%